IMPLEMENTASI LARANGAN PEMBUKAAN LAHAN DENGAN CARA MEMBAKAR - Sihombing, Rainer Wilona; Harahap, Irawan; Pardede, Rudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This provision is reinforced in Article 108, which stipulates that any person who carries out land burning as referred to in Article 69 paragraph (1) letter h shall be subject to imprisonment for a minimum of 3 (three) years and a maximum of 10 (ten) years, and a fine of at least IDR 3,000,000,000 (three billion rupiah) and at most IDR 10,000,000,000 (ten billion rupiah). This behavior not only disrupts public comfort due to the smoke produced but also causes environmental damage and air pollution, even though regulations prohibit such practices. The purpose of this research is to analyze the implementation of the prohibition on land clearing by burning based on Law Number 32 of 2009 in the jurisdiction of the Rokan Hulu Police, to examine the obstacles in its implementation, and to identify efforts to overcome these obstacles. The research method used is sociological juridical research. Based on the findings, the implementation of the prohibition has been carried out but not optimally. Communities continue to engage in small-scale burning in secret, especially at the beginning of the dry season. Although warning signs and banners prohibiting burning have been installed in several locations, supervision and patrols remain uneven. The main obstacles include the low awareness and understanding of the community regarding the environmental and legal impacts of burning, limited human resources and environmental investigation equipment, as well as difficulties in obtaining sufficient evidence and witnesses in the criminal process. Efforts to overcome these obstacles include enhancing environmental education and awareness programs for communities—particularly among farmers in fire-prone areas increasing the technical capacity of investigators through training on environmental law and fire forensics, and strengthening evidence collection using aerial monitoring technologies such as drones and GPS-based surveillance cameras to document burning locations as part of legal evidence.